Analisis Kinerja Petugas Kesehatan Terhadap Mutu Pelayanan Kesehatan Kepada Masyarakat - A.Syamsinar Asmi; Abdul Haris (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; community health center as the spearhead of health efforts both public health efforts and individual health efforts. Method; This study used a descriptive analytic method with a cross sectional study design. Sample 49 people with total sampling technique. Data were analyzed by univariate and bivariate with chi square statistical test using SPSS. Result; statistical test of educational outcomes (p = 0.453), facility factors (p = 0.265) that there is no relationship with the quality of health services, while work experience factors (p = 0.003) have a relationship with the quality of health services. Conclusion; that higher education and having good facilities are not always able to provide good health services to patients